Współczesne tendencje w teorii struktury kapitału i ich zastosowanie w warunkach polskich - Libura, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper presents modem capital structure theories emphasizing the importance of dynamic models. Dynamic models are considered to be the best to describe the complex reality. Therefore this article incorporates a brief description of KHH model which by using a dynamic adjustment approach identifies the determinants to capital structure. Moreover, the aim of the paper is to verify empirically whether the variables included in the model have an impact on capital structure of Polish firms. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 363-369